Адміністративно-правові засади здійснення контролю за якістю вищої освіти в Україні : автореферат дисертації - Невядовський, В. О.; Neviadovskyi, V. O.; Невядовский, В. О.; Vladyslav Neviadovskyi (Суми: Сумський державний університет, 2021)
У дисертації наведено теоретичне узагальнення та нове вирішення наукової проблеми – визначення сутності, змісту та розкриття особливостей адміністративно-правових засад здійснення контролю за якістю вищої освіти в Україні, що лягло в основу вироблення відповідної концепції, а також пропозицій і рекомендацій щодо вдосконалення законодавства у цій сфері. Доведено, що контроль як спосіб забезпечення законності діяльності закладів вищої освіти, – це особливий напрямок роботи уповноважених суб’єктів, який направлено на спостереження, аналіз та перевірку поточного стану функціонування відповідних закладів та її відповідності визначеним законодавством стандартам та вимогам. Встановлено, що предметом контролю за якістю вищої освіти в Україні є діяльність закладів вищої освіти, а також інших уповноважених суб’єктів щодо дотримання законодавчо визначених стандартів, ліцензійних вимог та державної політики в сфері вищої освіти. Узагальнено зарубіжний досвід контролю за якістю вищої освіти та опрацьовано можливості його використання в Україні.

The author of the dissertation has provided theoretical generalization and a new solution to the scientific problem – determining the essence, content and revealing specific features of administrative and legal principles of carrying out control over the quality of higher education in Ukraine, which formed the basis for elaborating the appropriate concept, as well as propositions and recommendations for improving legislation in this area. It has been stated that higher education as a socio-legal phenomenon has the following key features: first of all, higher education has a broad and high-quality system of normative and legal regulation, because a number of legislative and regulatory sources is focused on this issue; secondly, the state recognizes the special social value of higher education, and in this trgard forms and implements a separate branch of state policy in this area; thirdly, higher education has a significant social significance, since it provides systematic, continuous development of a person and the acquisition of professional skills and abilities that further help a person to choose a profession and place of work; fourth, higher education is the area of origin and existence of a large number of managerial relations that arise between a number of state authorities that make up the system of public administration of the education sector; fifth, higher education is consistent and structured, which involves that a person receives a consolidated “package” of knowledge, which ensures the continuous, consistent learning. It has been proved that control as the method to ensure the legitimacy of higher educational institutions’ activities is a special area of work of authorized entities, which is aimed at monitoring, analysis and verification of the current state of operation of relevant institutions and its compliance with statutory standards and requirements. The essence of the indicated control is expressed in the following: first of all, the existence of a multilevel management structure of higher education and the implementation of the state policy in this area; secondly, legally established strict and exclusive licensing requirements and standards of activities of higher educational institutions of Ukraine; thirdly, the existence of the accreditation procedure for verifying the status (level) of higher educational institutions; fourth, the systemic control, which includes control over the quality of higher education and maintaining this quality in higher educational institutions. It has been proved that the norms of administrative law occupy a key place among legal principles of control over the quality of education in Ukraine, because they assist: to regulate the operation procedure of control subjects, their structure and mutual subordination; to establish the features of implementing certain administrative procedures (for example, licensing and / or attestation); to put in order the list of functions and tasks in the field of control over the quality of higher education, etc. It is also important that the norms of the administrative branch of law enshrine the legal and organizational features of the interaction between the subjects of control in the researched area. It has been generalized that the subject matter of control over the quality of higher education in Ukraine is the activity of higher educational institutions, as well as other authorized entities regarding the compliance with statutory standards, licensing requirements and the state policy in the field of higher education. Thus, the subject matter of control is the entire complex of management and organizational activities in the field of higher education, which is aimed at maintaining the appropriate level of quality of both educational services and any other processes aimed at ensuring their quality. It has been emphasized that the importance of determining the subject matter of control is both theoretical and practical task, because this factor determines the boundaries of control over the quality of education in Ukraine. It has been established that the limits of control over the quality of higher education are expressed in the areas formed and determined in accordance with the subject matter of control: 1) legal institutions and mechanisms of control activities aimed at ensuring the compliance with the requirements and quality standards of higher education; 2) the wide range of powers of the parties of control over the quality of higher education in Ukraine; 3) administrative and other forms and methods of control over the quality of higher education defined and formed on the basis of legislation. It has been substantiated that the subjects of control over the quality of higher education in Ukraine should be considered from two aspects: first, as a set of authorized state agencies, which are endowed with powers to control activities in this direction in accordance with the current legislation; secondly, as a system of structural subdivisions of the respective higher educational institutions, the competences of which include the implementation of self-regulatory control over the quality of higher education. It has been stated that the classification of control over the quality of higher education should be based on a subjective criterion, which should prevent the incorrect definition of control types, in particular by identifying them with the forms. On this basis the author has distinguished the following: 1) state control; 2) self-regulatory and public control; 3) international control in the format of participation of subjects of international law in assessing the quality of higher education in Ukraine. It has been proved that the most useful for Ukraine aspects of international experience in carrying out control over the quality of higher education include the following: first of all, the optimal combination of ideas of a single educational European space with national educational traditions; secondly, the introduction of a comprehensive approach to control over the quality in higher education, which provides purely state and mixed control; thirdly, creating conditions for the functioning of various non-governmental organizations that have the right to carry out accreditation of high schools; fourth, accreditation agencies or foundations in foreign countries carry out accreditation not only of educational programs, but also institutional accreditation of higher educational institutions; fifthly, mandatory involvement of foreign experts to work in commissions that assess the quality of higher education is a widespread practice in foreign countries; sixth, the accreditation of higher educational institutions in the studied European countries takes place in several stages: self-examination (self-analysis, self-expertise), which is the basis for carrying out accreditation; external evaluation; introduction of recommendations and propositions into the work of the higher educational institution, which were developed during the monitoring; seventh, the main volume of work during the implementation of control procedures is mainly realized remotely through the appropriate means of electronic communication. Thus, it minimizes the number of direct personal contacts between the subject and the object of control, which increases the objectivity, impartiality and transparency of such control; eighth, special attention in European countries is paid to the participation in international monitoring programs and projects. It has been substantiated that it is expedient to introduce in Ukraine a combined approach to the criteria of assessing the effectiveness of carrying out control over the quality of higher education with the leading role of qualitative criteria, namely: 1) effectiveness and efficiency, which allow to evaluate whether the goals and objectives of control are achieved; 2) dynamism and intensity, which make it possible: to find out the number of control measures carried out for a certain period, the average period of their full implementation; to determine how changes in the intensity of control affect the quality of higher education; 3) normative and legal regulation. The analysis of control over this criterion is necessary in order to clarify whether the organizational and legal basis of control corresponds to the conceptual and strategic goals, to which it is focused on. That is, whether the control is able to actually provide the necessary results under the existing legal rules of its organization and implementation; 4) clarity and transparency, which allow determining how simple and unambiguous are the procedures and results of control for understanding by related parties. It is important to understand that such persons are both experts and students, their parents (persons who replace them); 5) professional opinion on the effectiveness of control over the quality of higher education. Evaluation according to this criterion involves the study of the opinions of employees of higher education, as well as specialized organizations, institutions engaged in practical and (or) research activities in the field of quality assurance of education; 6) public opinion – a criterion that involves the assessment of the effectiveness of control based on studying the opinion on this issue, especially users of educational services, as well as other interested citizens.

В диссертации приведены теоретическое обобщение и новое решение научной проблемы – определение сущности, содержания и раскрытия особенностей административно-правовых основ осуществления контроля качества высшего образования в Украине, что легло в основу выработки соответствующей концепции, а также предложений и рекомендаций по совершенствованию законодательства в этой сфере. Доказано, что контроль как способ обеспечения законности деятельности учреждений высшего образования – это особое направление работы уполномоченных субъектов, направленное на наблюдение, анализ и проверку текущего состояния функционирования соответствующих учреждений и его соответствия определенным. законодательством стандартам и требованиям. Установлено, что предметом контроля качества высшего образования в Украине является деятельность учреждений высшего образования, а также других уполномоченных субъектов по соблюдению законодательно определенных стандартов, лицензионных требований и государственной политики в сфере высшего образования. Обобщен зарубежный опыт контроля качества высшего образования и проработаны возможности его использования в Украине.
Автореферат дисертації на здобуття наукового ступеня доктора юридичних наук
Administrative and Legal Principles of Carrying out Control over Higher Education’s Quality in Ukraine
Невядовський, В. О. Адміністративно-правові засади здійснення контролю за якістю вищої освіти в Україні : автореф. дис. ... д-ра юрид. наук : 12.00.07, 081 / Невядовський Владислав Олегович; МВС України, Харків. нац. ун-т внутр. справ, МОН України, Сумс. держ. ун-т. - Суми, 2021. - 44 с.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Україна. Ukraine. Украина; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; адміністративно-правові засади; административно-правовые основы; administrative and legal principles; контроль; control; вища освіта; высшее образование; higher education; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; заклади вищої освіти; заведения высшего образования; institutions of higher education; якість освіти; качество образования; quality of education; зарубіжний досвід; зарубежный опыт; foreign experience; адміністративні процедури; административные процедуры; administrative procedures